2013
DOI: 10.1155/2013/810640
|View full text |Cite
|
Sign up to set email alerts
|

The Ruled Surfaces According to Bishop Frame in Minkowski 3-Space

Abstract: We investigate the ruled surfaces generated by a straight line in Bishop frame moving along a spacelike curve in Minkowski 3-space. We obtain the distribution parameters, mean curvatures. We give some results and theorems related to be developable and minimal of them. Furthermore, we show that, if the base curve of the ruled surface is also an asymtotic curve and striction line, then the ruled surface is developable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…We know that the properties of geometric objects are independent of the choice of the coordinate systems. But, the researchers found that, when they adopted this frame, there will be some new geometric objects such as parallel slant curves, Bishop spherical images, Bishop Darboux images, etc.. After that, many regular curves and surfaces related to the Bishop frame have been treated in the Euclidean space [5, 6, 13-17, 22, 24], Minkowski space [4,21,23,26], dual space [11] and Heisenberg group Heis 3 [12]. The current study hopes to research those singular curves and surfaces associate to the Bishop frame instead of regular ones.…”
Section: Introductionmentioning
confidence: 99%
“…We know that the properties of geometric objects are independent of the choice of the coordinate systems. But, the researchers found that, when they adopted this frame, there will be some new geometric objects such as parallel slant curves, Bishop spherical images, Bishop Darboux images, etc.. After that, many regular curves and surfaces related to the Bishop frame have been treated in the Euclidean space [5, 6, 13-17, 22, 24], Minkowski space [4,21,23,26], dual space [11] and Heisenberg group Heis 3 [12]. The current study hopes to research those singular curves and surfaces associate to the Bishop frame instead of regular ones.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the work of Bishop, in [19], the authors introduced a new version of Bishop frame using a common vector field as binormal vector field of a regular curve and called this frame as "Type-2 Bishop frame". There are many applications of Bishop frames in differential geometry such as [1, 3,8,9,10,11,12,17,19,20]. Up to now, different types of surfaces and curves such as ruled surfaces [9,20], tubular surfaces [8], special Bishop motion and Bishop Darboux rotation axis of the space curve [3] and B-canal surfaces in terms of biharmonic B-slant helices in Heisenberg group Heis 3 [10] have been studied according to Bishop frames.…”
Section: Introductionmentioning
confidence: 99%
“…There are many applications of Bishop frames in differential geometry such as [1, 3,8,9,10,11,12,17,19,20]. Up to now, different types of surfaces and curves such as ruled surfaces [9,20], tubular surfaces [8], special Bishop motion and Bishop Darboux rotation axis of the space curve [3] and B-canal surfaces in terms of biharmonic B-slant helices in Heisenberg group Heis 3 [10] have been studied according to Bishop frames. Inspired by the work of Bishop, in [9], the authors introduced the ruled surface with Bishop frame N 2 (s) as its directrix, i.e., ϕ(s, t) = γ(s) + uN 2 (s), which they also called N 2 (s)-ruled surface with the Bishop frame.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations